Religious Bourgeois Lifestyle of Celebrity Hijrah: Reading the Resurrection of the Muslim Middle Class Based on Cultural Imperalism and Global Economic Factors - Sunaryanto Sunaryanto; Sofyan Rizal; Zulkifli Zulkifli (MUHARRIK: Jurnal Dakwah dan Sosial, 2022)
This paper attempts to analyze the bourgeois religious lifestyle of celebrities' hijrah from the perspective of globalization by focusing on how imperialism influences this lifestyle and why it is in line with the global economy. The theory used is the globalization theory of Gill Branston and Roy Stafford. The qualitative research approach is based on online and printed literature from books, websites, journals, and relevant research results. After the data is collected, the data analysis uses the interactive model of Miles and Huberman, namely data reduction, data display, interpretation, and conclusion. This study concludes that a bourgeois religious lifestyle is a form of Islamic identity for hijrah celebrities. The lifestyle displayed is bourgeois but does not leave Islam a symbol of Piety. The interpretation of the hijrah celebrity towards globalization is to construct it as a religious bourgeois identity. Cultural imperialism is a factor in forming the religious bourgeois lifestyle of celebrities who migrate in the identity displayed in the public space outside the network and in the public space in the network. The bourgeois religious lifestyle of hijrah celebrities can be in line with the interests of the global economy because they both need and complement each other.